Effect of Anesthesia on Oligodendrocyte Development in the Brain - Fu, Ningning; Zhu, Ruilou; Zeng, Shuang; Li, Ningning; Zhang, Jiaqiang (Frontiers in Systems Neuroscience, 2022)
Oligodendrocytes (OLs) are myelin forming cells in the central nervous system (CNS) that participate in the formation of myelin sheaths that facilitate action potential propagation, and disruption of their proliferation and differentiation leads to damage to the CNS. As surgical techniques have advanced, there is an increasing number of children who undergo multiple procedures early in birth, and recent experiments have demonstrated effects on brain development after a single or multiple anesthetics. An increasing number of clinical studies showing the effects of anaesthetic drugs on the development of the nervous system may mainly reside in the connections between neurons, where myelin development will receive more research attention. In this article, we review the relationship between anesthesia exposure and the brain and OLs, and provide new insights into the development of the relationship between anesthesia exposure and OLs, providing a theoretical basis for clinical prevention of neurodevelopmental risks from general anesthesia drugs.